Religion and the Sciences of Origins - Clark, Kelly James. author. aut Link
IX, 274 p.
Keywords: This concise introduction to science and religion focuses on Christianity and modern Western science (the epicenter of issues in science and religion in the West) with a concluding chapter on Muslim and Jewish Science and Religion. This book also invites the reader into the relevant literature with ample quotations from original texts.